A Reassessment of Lateral Nail-bearing Strength of Terminalia alata (Sain) with 3.55 Mm Dia Common Wire-nails under Double Shear (Parallel and Perpendicular-to-grain Loadings) - Pruthi, K. S.; Lal, Mohan (Indian Forester, 1994)
Nail is an economical and simple jointing device for wood in timber structure such as roof trusses, columns etc. The lateral bearing strength of 3.55 mm dia (9 SWG) nails in double shear in Terminalia alata (Sain) now redetermined through laboratory tests for parallel and perpendicular to grain loadings has heen reported in this paper based on the requirements of Indian Standard. The data will enable the engineers to design and construct safe timber stroetures more economically.